2009
DOI: 10.1093/annonc/mdn683
|View full text |Cite
|
Sign up to set email alerts
|

Age and HER2 expression status affect MRI accuracy in predicting residual tumor extent after neo-adjuvant systemic treatment

Abstract: Background: Although recent studies suggest high accuracy of breast magnetic resonance imaging (MRI) in predicting residual tumor extent after neo-adjuvant systemic treatment (NST), its use is still controversial. In this study, we aimed to identify predictive factors of MRI accuracy after NST to determine a subgroup of patients in whom the use of MRI provides best additional benefit. Materials and methods:Clinicopathologic and molecular profiles of breast cancer patients were investigated and their relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…9,13,22 For HER2 positive cancer, which is very sensitive to the targeted therapy trastuzumab and chemotherapy, and generally highly proliferative, the treatment is more likely to eliminate the scattered residual cancer cells, leading to a higher negative predictive value of MRI. 28 For HER2 negative cancer, there is no effective targeted regimen, and the residual disease is likely to present as scattered cells and difficult to diagnose by MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,13,22 For HER2 positive cancer, which is very sensitive to the targeted therapy trastuzumab and chemotherapy, and generally highly proliferative, the treatment is more likely to eliminate the scattered residual cancer cells, leading to a higher negative predictive value of MRI. 28 For HER2 negative cancer, there is no effective targeted regimen, and the residual disease is likely to present as scattered cells and difficult to diagnose by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…9-11 Despite superior accuracy when compared with other modalities, MRI can over- or under- estimate residual tumor extent. This inaccurate assessment may be influenced by tumor response (some tumors shrink concentrically down to a single focus of residual tumor cells, while others break apart into scattered tumor cells in patchy patterns 4 ), chemotherapeutic agent, or NAC-induced reactive changes within the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published datasets have shown that MRI most accurately predicts the amount of residual pathologic disease in HR-negative subtypes rather than HR-positive subtypes (11,(16)(17)(18)(19). The concept of variation in clinical response evaluation accuracy by breast cancer subtype is important for the design of future response-guided NACT trials.…”
Section: Figure 2 Positive Predictive Value (Ppv) (A) and False-posimentioning
confidence: 99%
“…Recent studies have shown that the accuracy of imaging in clinical response evaluation varies by breast cancer subtype according to HR and HER2 status (11)(12)(13)(14)(15)(16)(17)(18)(19). Specifically, MRI more accurately predicts pathologic response in HR-negative subtypes rather than HRpositive stubtypes (11,(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…[34][35][36][37] Although some have reported the highest accuracy of MRI for Her2-disease, not knowing HR status and differences in rates of traztuzumab use could potentially account for the disparate results. 38 Benign proliferative processes can enhance on MRI and are difficult to differentiate from low-grade, ER? DCIS lesions.…”
Section: Discussionmentioning
confidence: 99%